Measuring Health-Related Quality of Life: General Issues - Gordon H Guyatt (Canadian Respiratory Journal)
Clinicians and policy makers recognize the importance of measuring health-related quality of life (HRQL) to make informed patient management and policy decisions. Self- or interviewer-administered questionnaires can be used to measure cross-sectional differences in quality of life among patients at a point in time (discriminative instruments) or longitudinal changes in HRQL within patients over time (evaluative instruments). Both discriminative and evaluative instruments must be valid (ie, measure what they are supposed to measure) and have a high ratio of signal to noise (reliability and responsiveness for the two instruments, respectively). Reliable discriminative instruments are able to differentiate reproducibly among persons. Responsive evaluative measures are able to detect important changes in HRQL over time, even if those changes are small. HRQL should also be interpretable B that is, clinicians and policy makers must be able to identify differences in scores that correspond to trivial, small, moderate and large differences.